2011
DOI: 10.1159/000324474
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Overexpression in Oxygen-Induced Retinopathy Correlates with Breakdown of the Blood-Retina Barrier and Retinal Neovascularization

Abstract: Purposes: Recent research has shown netrin-1 to promote neovascularization. We evaluate the expression of netrin-1 during retinal neovascularization in a murine model of oxygen-induced retinopathy. Methods: C57BL/6J mice were exposed to 75 ± 5% oxygen for 5 days and returned to room air to induce retinal neovascularization. Retinal neovascularization was observed by fluorescence angiography and was quantified by counting the endothelial nuclei protruding into the vitreous cavity after hematoxylin-eosin stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Administration of recombinant netrin-1 or overexpression of netrin-1 improved conductance velocity of nerves and increased angiogenesis in diabetic mice [18]. More recently, diabetic retinopathy was associated with increased levels of netrin-1 in the vitreous fluid [19, 20]. Studies from our laboratory had shown that epithelial cell-derived netrin-1 may reduce albuminuria and interstitial fibrosis through suppression of inflammation and increased uptake of albumin [21].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of recombinant netrin-1 or overexpression of netrin-1 improved conductance velocity of nerves and increased angiogenesis in diabetic mice [18]. More recently, diabetic retinopathy was associated with increased levels of netrin-1 in the vitreous fluid [19, 20]. Studies from our laboratory had shown that epithelial cell-derived netrin-1 may reduce albuminuria and interstitial fibrosis through suppression of inflammation and increased uptake of albumin [21].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggest that administration of recombinant netrin-1 or overexpression of netrin-1 improved conductance velocity of nerves and increases angiogenesis in diabetic mice [18]. More recently, diabetic retinopathy was associated with increased levels of netrin-1 in the vitrous fluid [19;20]. However, the exact role of netrin-1 in diabetic complications is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In ROP, netrin‐1 has been reported by several studies to promote developmental and pathological angiogenesis in the retina . For instance, Tian et al.…”
Section: Pathological Intravitreal Neovascularisationmentioning
confidence: 99%
“…For instance, Tian et al. showed that the expression levels of netrin‐1 were significantly upregulated during neovascular formation. They also showed that netrin‐1 not only participates in pathological angiogenesis, but can also induce retinal vascular permeability.…”
Section: Pathological Intravitreal Neovascularisationmentioning
confidence: 99%